Natural products as metabolic modulators to enhance cancer immunotherapy: reprogramming the tumor microenvironment - Fan, Xiaoyu; Guo, Shushu; Li, Wanfang; Wang, Yingyin; Bao, Jie; He, Jiuming; Jin, Hongtao (Frontiers in Immunology, 2026)
Cancer remains a major global health challenge, and although immunotherapy has achieved remarkable breakthroughs, its efficacy is often limited by tumor-induced immunosuppression within the tumor microenvironment (TME). Emerging evidence indicates that metabolic reprogramming plays a pivotal role in shaping the TME and regulating antitumor immune responses. Targeting tumor and immune cell metabolism has therefore become a promising strategy to enhance the effectiveness of cancer immunotherapy. This review first summarizes the metabolic reprogramming that occurs within the TME, including alterations in glucose, lipid, and amino acid metabolism in tumor cells, as well as the metabolic adaptation of immune cells. We then highlight recent advances in natural products that modulate key metabolic pathways and their potential to reshape the immunosuppressive TME. Special emphasis is placed on natural compounds that not only inhibit tumor cell metabolism but also restore the metabolic fitness of immune cells, thereby improving antitumor immunity. In addition, advances in delivery strategies, including nanocarrier-based and stimuli-responsive systems, are reviewed for their roles in improving the bioavailability, stability, and tumor targeting of natural metabolism-regulating agents. Finally, we discuss the current status and challenges of translating natural metabolism-regulating agents into clinical applications, including issues of dose optimization, safety evaluation, and patient selection. Despite these hurdles, precision targeting of metabolic pathways, interdisciplinary collaboration, and the discovery of novel compounds—particularly immune-sensitizing agents derived from traditional medicine—are expected to accelerate progress. Collectively, natural products represent promising adjuvant strategies for cancer immunotherapy, with great potential to overcome current therapeutic limitations and improve clinical outcomes.